Investigating the Implementation of 2013 Revised Curriculum and School-Based Curriculum from Postmethod Pedagogy Principle: Teachers’ Perspective - Muhammad Anjar Nugraha; Slamet Wahyudi Yulianto (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2020)
Take-in the ever-changing policy of Education in Indonesia seems a very long-crucial issue to be discussed. Post-method pedagogy offers with the controversial claim that in the 21st era the play of teaching method is dying. Post-method pedagogy is the current issue of English Language Teaching (ELT) nowadays. This is a qualitative case study aims at investigating English teachers’ perspective towards post-method pedagogy. English teachers from two senior high schools in Subang has taken as the participants. A school is a public school, in which implements 2013 revised-curriculum and one another school is a private school that implements a School-based Curriculum or integrated curriculum. Those teachers administered the questionnaire and one teacher for each school will be chosen to conduct classroom observation and semi-structured interviews. According to the result of this study, the researcher indicates that all the participants tend to implement Communicative Approaches-Communicative Language Teaching (CLT)-Task Based Language Teaching most in their future classes. Eventhough the participants have their own style of teaching, they are not believe in themselves enough to produce their own teaching method. They have an authority to combine and prove it with their beliefs and background knowledge. They pay attention to the background of language learner and should not only focus on native speakers’ value. The researcher is almost able to observe the macro strategies that purposed by Kumaravadivelu. There is no difference between teacher who implements the 2013 revised curriculum and school-based curriculum or integrated curriculum from post method pedagogy principle